STRATEGI BERSAING PADA INDUSTRI KERUPUK AMPLANG - Syaifur Rahman; Banun Diyah Probowati; Supriyanto Supriyanto (Agroindustrial Technology, University of Trunojoyo Madura, 2014)
Amplang crackers processing industry is an industry with the use of raw materials mackerel. The industry experienced a decline in competitiveness characterized by a decrease in the amount of production and sales. The purpose of this study was to determine the application of competitive strategy undertaken by the company and to determine the competitive strategy that should be done by the company in an effort to increase sales turnover. Data analysis methods used in this study are IFAS matrix, the matrix EFAS, IE matrix, SWOT matrix. The results showed that there were internal factors to play role as the strength of the industry: (1) the production unit is close to the source of raw materials, (2) good raw material quality, (3) the quality attributes that can satisfy consumers, (4) relatively high venture capital, (5) the involvement of the family in a fairly large extent (0.239), (6) the products are on the market, (7) relatively simple technology used in production, (8) the volume of product sales constantly increased annually. However, there were internal factors that contributed to the weaknesses of this industry:(1) low level of workforce education, (2) seasonal supply of raw material, (3) limited facilities and infrastructure distribution of products, (4) not using diverse means of promotion, (5) production siteis away from the product market. The external factors positively influence the cracker industry were: (1) increasingly high customer loyalty, (2) large market segment, (3) high sale potential, (4) supportive business climate. External factors that were considered as threats were:(1) new competitors, (2) supply of raw materials is dependent of natural conditions. Based on the SWOT analysis of SO strategy, the most appropriate strategy was to increase the availability of products in the market. SO strategy is used as a basis to support aggressive growth policy